Using post-cracking strength to determine flexural capacity of ultra-thin whitetopping (UTW) pavements. (20th April 2020) - Suksawang, Nakin; Alsabbagh, Ahmed; Shaban, Alaa; Wtaife, Salam
Highlights: Various fibers content, UTW thickness and failure modes have been tested. FRC/asphalt composite beam should be considered in the UTW design. Using the effective MOR concept reduces the required UTW thickness. ASTM C78 formula does not show the fiber's benefits in the UTW. Post-cracking strength should be used to quantify the added capacity of fibers. Abstract: Utilizing fibrillated polypropylene fibers (FPP) in Ultra-thin whitetopping (UTW) has become increasingly popular to improve the flexural capacity of concrete slabs. The calculated flexural strength (i.e., modulus of rupture (MOR)) depends on the elastic formula of ASTM C78 does not illustrate the fiber's benefits. Therefore, the concept of effective modulus of rupture (MOR eff .) that is determined from the equivalent flexural strength ratio has been used to quantify the added flexural capacity of fibers on unreinforced concrete. The purpose of this study is to investigate the benefits of testing the FRC/asphalt composite beam on the flexural capacity of UTW. Three main parameters have been taken into consideration: FPP content, pavement thickness, and failure mode. Furthermore, comparison was made to verify the effectiveness of composite beams for flexural capacity. Six different cases of concrete beams and ten cases of FRC/asphalt composite beams were performed. The results of the composite beam showed that the flexural capacity was higher than the capacity of the concrete layer. In addition, using FPP in the composite beams improved the MOR eff. . The results also revealed that testing UTW under noncommon failure modes did not reflect the real flexural capacity of UTW. The required UTW thickness depends on the proposed flexural capacity of the composite beam being less than the required thickness that is calculated depends on the concrete beam.